Teaching Comparative Law in Eighteenth-Century England: Thomas Bever as a Comparative Lawyer as Exemplified by his Lectures on Polish Law and the Constitution - Korporowicz, Łukasz Jan (Acta Universitatis Lodziensis. Folia Iuridica, 2022)
The origins of comparative legal studies usually date back to the late 19th century. These kind of studies, however, were undertaken on a regular basis much earlier. Among the first serious adherents of the idea of comparing different legal systems was Thomas Bever. Bever was a civilian lawyer who successfully combined practice in the ecclesiastical and admiralty courts of England with Oxford’s fellowship and teaching duties. In the 1760s and 1770s, Bever was teaching the Civil law course on behalf of (or independently of) the current holders of the Regius Professorship. His lectures, unique in many aspects, were crowned with a set of comparative lectures. Bever was presenting the constitutional and legal systems of several European countries, including Poland, both in historical and modern dimensions. The aim of this article is to discuss Bever’s attitude towards comparative legal studies as well as to present his comparative method by reference to part of his lectures devoted to the old Polish law and constitution.